PeerJ Analytical Chemistry 2020
DOI: 10.7717/peerj-achem.6
|View full text |Cite
|
Sign up to set email alerts
|

Establishing an optimized method for the separation of low and high abundance blood plasma proteins

Abstract: The study tested the efficiency and reproducibility of a method for optimal separation of low and high abundant proteins in blood plasma. Firstly, three methods for the separation and concentration of eluted (E: low abundance), or bound (B: high abundance) proteins were investigated: TCA protein precipitation, the ReadyPrep™ 2-D cleanup Kit and Vivaspin Turbo 4, 5 kDa ultrafiltration units. Secondly, the efficiency and reproducibility of a Seppro column or a ProteoExtract Albumin/IgG column were assessed by qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
1
0
1
Order By: Relevance
“…Protein separation by ultrafiltration showed that the value of protein content was largest at MW ≥5 kDa and that the low MW fraction after ultrafiltration was used for determining the bioactive peptide potency for ACE-1 testing. The higher protein content determined by ultrafiltration has been found at higher ultrafiltration size (more than 5 kDa); however, the protein obtained by enzymatic hydrolysis will be more efficacious [22]. Protein levels obtained were conducted by three repetitions and had significant (p<0.05) differences in terms of the ultrafiltration size.…”
Section: Protein Concentrationmentioning
confidence: 96%
“…Protein separation by ultrafiltration showed that the value of protein content was largest at MW ≥5 kDa and that the low MW fraction after ultrafiltration was used for determining the bioactive peptide potency for ACE-1 testing. The higher protein content determined by ultrafiltration has been found at higher ultrafiltration size (more than 5 kDa); however, the protein obtained by enzymatic hydrolysis will be more efficacious [22]. Protein levels obtained were conducted by three repetitions and had significant (p<0.05) differences in terms of the ultrafiltration size.…”
Section: Protein Concentrationmentioning
confidence: 96%
“…CB-PHEMA mikroküreler ile saf RuBisCO çözeltilerinden adsorpsiyon sonrasında protein bantlarının yoğunluğunun azaldığı ve bant yoğunluklarındaki azalışın, artan CB-PHEMA miktarı ile arttığı belirlendi. [10,34,35]. Bitki proteom çalışmalarında, fotosentetik bitki dokularında biyobelirteç olarak kullanılabilecek fonksiyonel proteinlerin saptanmasında RuBisCO çok önemli bir sınırlayıcı proteindir [10].…”
Section: İzotermal Kinetik Ve Termodinamik Analizlerunclassified